Hydrogen storage material and preparation method thereof

By using a ceramic layer and resin filled structure in the hydrogen storage tank, the problems of thinning of the inner liner, decreasing sealing performance and deforming resistance caused by volume changes in the carbon fiber hydrogen storage tank under large volume conditions are solved, and carbon fiber is reduced The effect of dosage, improving insulation performance and reducing the risk of hydrogen leakage.

CN119412604AActive Publication Date: 2025-02-11YANCHENG TEACHERS UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411889876.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When the volume of existing carbon fiber hydrogen storage tanks exceeds 400 liters, volume changes lead to local thinning of the inner liner, deterioration of sealing performance and deforming resistance, increasing hydrogen leakage and safety risks.

Method used

The hydrogen storage material structure is adopted, including the inner liner, the pressure-resistant layer, the ceramic layer and the outer protective layer from the inside to the outside. The thickness of the ceramic layer is 20mm~50mm, the tensile strength is ≥180MPa, and the ceramic layer and the pressure-resistant layer are filled with the second A resin is filled with a second resin between the outer protective layer and the ceramic layer.

Benefits of technology

The ceramic layer shares part of the pressure, reduces the thickness of the pressure-resistant layer, reduces the amount of carbon fiber and manufacturing cost, improves the insulation performance and overall reliability of hydrogen storage materials, and reduces the risk of hydrogen leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119412604A_ABST
    Figure CN119412604A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogen storage material and a preparation method thereof. The hydrogen storage material sequentially comprises an inner container, a pressure-resistant layer, a ceramic layer and an outer protective layer from inside to outside, the thickness of the ceramic layer is 20-50mm, and the tensile strength of the ceramic layer is greater than or equal to 180MPa; the inner diameter of the ceramic layer is equal to or in over-virtual fit with the outer diameter of the pressure-resistant layer, first resin is filled between the ceramic layer and the pressure-resistant layer, and the compressive strength of the first resin is larger than or equal to 70 MPa; the outer protective layer is made of a hard material, a second resin is filled between the ceramic layer and the outer protective layer, and the second resin comprises a vinyl resin; the preparation method of the hydrogen storage material comprises the steps of carbon fiber impregnation and winding, curing of the pressure-resistant layer, filling and curing of the first resin and filling and curing of the second resin. The hydrogen storage material provided by the invention has the effect of reducing the risk of hydrogen leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen storage, and in particular, relates to a hydrogen storage material and a preparation method thereof. Background Art

[0002] Hydrogen, as a gas with extremely high weight energy density, is regarded as the most promising clean energy carrier of this century because of its clean combustion, pollution-free and wide source. However, hydrogen storage technology is the key bottleneck to realize the hydrogen economy. At present, high-pressure containers show the greatest practical application value among various hydrogen energy storage media.

[0003] Type IV hydrogen storage tank is a technologically advanced high-pressure hydrogen storage container, which is widely used in hydrogen fuel cell vehicles, hydrogen transportation and other fields. Its structure mainly consists of three parts: inner tank, pressure-resistant layer and outer protective layer. According to the national standard "Hydrogen Storage and Transportation System Part 1: General Requirements", the working pressure of Type IV hydrogen storage tank is not more than 140MP.

[0004] The wall thickness of the liner is usually between 2 and 3 mm, and it is mainly made of polymer materials. Commonly used materials include PA6 (nylon 6), PA612, PA11 and HDPE (high-density polyethylene), which are selected for their good hydrogen barrier properties, heat resistance and mechanical strength.

[0005] The pressure-resistant layer is mainly composed of carbon fiber. The carbon fiber hydrogen storage tank has the characteristics of light weight, high strength, fatigue resistance and excellent corrosion resistance. It is worth noting that in the carbon fiber hydrogen storage tank, the internal pressure is completely borne by the reinforcing fibers. In order to ensure safety performance, the actual required thickness of the carbon fiber layer is often far greater than the thickness required to meet only the working pressure of 140MPa. This design leads to a significant increase in the amount of carbon fiber used, which in turn increases the overall weight of the carbon fiber hydrogen storage tank. At the same time, due to the relatively high price of carbon fiber materials, the manufacturing cost of carbon fiber hydrogen storage tanks is also high when the amount of carbon fiber used is large.

[0006] In addition, although carbon fiber has the significant advantages of high strength and small deformation, for a carbon fiber hydrogen storage tank with a volume of more than 400 liters, its volume will change significantly before and after filling with hydrogen. This change will have the following specific effects:

[0007] ① During the hydrogen filling process, as the pressure inside the hydrogen storage tank increases, the tank volume will expand. Therefore, the liner needs to adapt to this volume change, but this process may cause the liner to become locally thinner or have tiny tears, thereby increasing the risk of hydrogen leakage.

[0008] ② The sealing components of the hydrogen storage tank will also reduce the tightness of the connection with the pipe body due to volume changes, which will lead to a decrease in sealing performance and also increase the risk of hydrogen leakage.

[0009] ③ When the volume of a hydrogen storage tank exceeds 400 liters, its overall anti-deformation ability will gradually decrease as the volume increases. Therefore, hydrogen storage tanks with a volume of more than 400 liters are prone to deformation due to external forces during transportation. During the deformation of the hydrogen storage tank, carbon fiber breakage and loose carbon fiber layer structure may occur, seriously affecting the durability and safety of the hydrogen storage tank. Summary of the invention

[0010] In view of the deficiencies of the prior art, an object of the present invention is to provide a hydrogen storage material and a preparation method thereof.

[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0012] On the one hand, a hydrogen storage material includes, from inside to outside, an inner liner, a pressure-resistant layer, a ceramic layer, and an outer protective layer;

[0013] The thickness of the ceramic layer is 20 mm to 50 mm, and the tensile strength of the ceramic layer is ≥ 180 MPa;

[0014] The inner diameter of the ceramic layer is equal to or overfits with the outer diameter of the pressure-resistant layer, a first resin is filled between the ceramic layer and the pressure-resistant layer, and the compressive strength of the first resin is ≥70MPa;

[0015] The outer protective layer is a hard material, and a second resin is filled between the ceramic layer and the outer protective layer, wherein the second resin includes a vinyl resin.

[0016] In the present invention, the first resin can play a role in transmitting force, so that the ceramic layer and the pressure-resistant layer can bear pressure together; because the ceramic layer can share part of the pressure, the pressure-resistant layer does not need to bear all the pressure, which is conducive to reducing the thickness of the pressure-resistant layer.

[0017] In the present invention, the vinyl resin is selected from one or more of bisphenol A epoxy vinyl resin, phenolic epoxy vinyl ester, acrylic vinyl ester resin, and flexible vinyl ester resin.

[0018] In the present invention, the tensile strength of the ceramic layer is generally greater than 200 MPa.

[0019] In the present invention, the pressure-resistant layer is usually made of carbon fiber, the surface of the pressure-resistant layer is not a standard smooth surface, the inner diameter of the ceramic layer is equal to the outer diameter of the pressure-resistant layer or is overly matched, which is conducive to the full fit between the ceramic layer and the pressure-resistant layer. The first resin can fill the gap between the ceramic layer and the pressure-resistant layer, which is conducive to the transmission of force between the ceramic layer and the pressure-resistant layer.

[0020] Preferably, the pressure-resistant layer has a pressure resistance of P 1 The ceramic layer withstands a pressure of P2 , P 1 +P 2 ≥140MPa.

[0021] Preferably, the compressive strength of the first resin is P 3 , P 2 -P 1 ≤P 3 .

[0022] Preferably, when the hydrogen storage material stores hydrogen, the gas pressure in the inner container is P 4 , P 4 ≥P 1 .

[0023] In the present invention, 40MPa≤P 4 ≤70MPa.

[0024] Preferably, the first resin is the resin used for the pressure-resistant layer.

[0025] In the present invention, the first resin is the same as the resin used in the pressure-resistant layer, which can reduce the poor compatibility between the first resin and the pressure-resistant layer due to different resin properties; at the same time, the first resin is the same as the resin used in the pressure-resistant layer, so that the first resin and the resin used in the pressure-resistant layer are cured at the same time, which is beneficial to improving the integrity of the first resin and the pressure-resistant layer.

[0026] Preferably, the second resin is cured at room temperature.

[0027] In the present invention, the second resin is cured at room temperature, which can prevent the first resin from being over-cured due to high temperature again.

[0028] In the present invention, the vinyl resin is specifically selected from bisphenol A epoxy vinyl resin.

[0029] Preferably, the second resin is a foamed resin.

[0030] In the present invention, the foamed resin has good thermal insulation performance, which is beneficial to heat preservation of the stored hydrogen; at the same time, the foamed resin has the function of absorbing vibration and reducing mechanical impact, so as to protect the ceramic layer.

[0031] Preferably, the second resin has a thickness of 5 mm to 15 mm.

[0032] Preferably, the material of the ceramic layer is selected from one or more of aluminum oxide, silicon nitride, zirconium oxide and silicon carbide.

[0033] In the present application, the material of the ceramic layer is specifically selected from aluminum oxide, silicon nitride and zirconium oxide.

[0034] Preferably, the material of the outer protective layer is selected from metal and plastic.

[0035] In the present application, the material of the outer protective layer is specifically selected from 302 stainless steel.

[0036] In another aspect, a method for preparing a hydrogen storage material comprises the following steps:

[0037] S1, dipping the carbon fiber in glue and winding it on the inner liner to obtain an uncured pressure-resistant layer;

[0038] S2, curing the pressure-resistant layer;

[0039] S3, coating the inner surface of the ceramic layer with a first resin, installing the pressure-resistant layer into the ceramic layer, and then curing the first resin;

[0040] S4, installing the pressure-resistant layer into the outer protective layer, filling the second resin between the pressure-resistant layer and the outer protective layer, and then curing the second resin to obtain the hydrogen storage material.

[0041] Preferably, the uncured pressure-resistant layer in step S1 is cured simultaneously with the first resin, and the method includes: coating the first resin on the surface of the ceramic layer, then loading the uncured pressure-resistant layer in step S1 into the ceramic layer, then degassing the pressure-resistant layer and the first resin at the same time, and then curing the pressure-resistant layer and the first resin at the same time.

[0042] In the present invention, compared with curing the pressure-resistant layer and the first resin step by step, the pressure-resistant layer and the first resin can form a whole after being cured simultaneously, which is beneficial to the transmission of force between the ceramic layer and the pressure-resistant layer.

[0043] During the production process of the pressure-resistant layer, the viscosity of the resin has a significant impact on the performance of the pressure-resistant layer after molding, which is specifically reflected in the following aspects:

[0044] ① Increasing the viscosity of the resin is beneficial to improving the mechanical properties of the pressure-resistant layer. However, this measure will make it difficult to effectively discharge bubbles during the degassing process, thereby prolonging the degassing time. Especially in the wet winding method, the carbon fiber winding process itself is time-consuming, and coupled with the limitation of the resin's applicable period, the viscosity of the resin used in the production process of the pressure-resistant layer is strictly limited.

[0045] ② Although reducing the viscosity of the resin is beneficial to the degassing process of the pressure-resistant layer before curing, the low-viscosity resin is difficult to fully impregnate the carbon fiber, which in turn affects the strength and uniformity of the composite material.

[0046] Therefore, during the production process of the pressure-resistant layer, there is a contradiction between the need to increase the viscosity of the resin and the need to reduce the viscosity of the resin.

[0047] In addition, during the degassing process of the pressure-resistant layer, after the internal bubbles escape, due to the limited amount of resin adhering to the carbon fiber, the discharge of bubbles will cause uneven resin distribution in certain areas, affecting the impact resistance and damage resistance of the pressure-resistant layer.

[0048] Compared with the prior art, the thickness of the pressure-resistant layer in the present invention is small, which will have the following effects:

[0049] ① The small thickness of the pressure-resistant layer is conducive to reducing the difficulty of degassing and shortening the degassing time. At the same time, as the thickness of the pressure-resistant layer is reduced, the amount of resin required is also reduced accordingly, which further helps to shorten the degassing time.

[0050] ② A small thickness of the pressure-resistant layer is also conducive to reducing the time required for wet winding, leaving more time for the degassing process, thereby improving the degassing effect. In addition, a reduced thickness of the pressure-resistant layer is also conducive to shortening the heating time, thereby shortening the curing time of the pressure-resistant layer and improving the preparation efficiency.

[0051] ③The small thickness of the pressure-resistant layer is conducive to reducing the time required for wet winding, so that more time can be reserved for the degassing process, which is conducive to improving the degassing effect;

[0052] In addition, after the pressure-resistant layer is loaded with the ceramic layer, the uncured pressure-resistant layer is soaked in the first resin. When the pressure-resistant layer and the first resin are degassed at the same time, the fluidity of the first resin can make up for the defects caused by the escape of bubbles, thereby improving the overall performance of the pressure-resistant layer.

[0053] Preferably, the method of coating the inner surface of the ceramic layer with the first resin in step S3 includes: filling the ceramic layer with the first resin for infiltration for 0.5 hours, and then pouring out the first resin to obtain a ceramic layer with the inner surface coated with the first resin.

[0054] In the present invention, the first resin infiltrates the ceramic layer, which is beneficial to the combination of the first resin and the ceramic layer, thereby facilitating full contact between the first resin and the ceramic layer and improving the uniformity of force transmission between the first resin and the ceramic layer.

[0055] Compared with the prior art, the advantages of the present invention include:

[0056] (1) In the hydrogen storage material provided by the present invention, the second resin has good thermal insulation performance, which is beneficial to improving the thermal insulation performance of the hydrogen storage material; at the same time, the second resin can maintain good elasticity at low temperatures, thereby effectively protecting the ceramic layer, overcoming the defect of the ceramic being fragile, and improving the overall reliability and service life of the hydrogen storage material.

[0057] (2) The hydrogen storage material provided by the present invention is conducive to reducing the thickness of the pressure-resistant layer because the ceramic layer and the pressure-resistant layer can bear pressure together, which not only reduces the amount of carbon fiber used, reduces the difficulty and time of degassing, but also shortens the curing time of the pressure-resistant layer, thereby reducing the manufacturing cost of the hydrogen storage material and improving the preparation efficiency;

[0058] (3) The present invention provides a hydrogen storage material. Currently, the technology for recycling carbon fiber is still immature. By reducing the amount of carbon fiber used, it is beneficial to reduce the generation of carbon fiber waste, which has positive significance for environmental protection.

[0059] (4) The hydrogen storage material provided by the present invention has a ceramic layer with good pressure bearing capacity and deformation resistance. Therefore, when the hydrogen storage tank is large in size, the ceramic layer can limit the deformation of the pressure-resistant layer, thereby reducing the overall deformation of the hydrogen storage tank and reducing the risk of hydrogen leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0061] Figure 1 It is an overall schematic diagram of the hydrogen storage bottle in the present invention;

[0062] Figure 2 This is a schematic diagram of the interior of the hydrogen storage bottle of the present invention;

[0063] Figure 3 for Figure 2 The enlarged schematic diagram of the middle A part;

[0064] Figure 4 It is a cross-sectional schematic diagram of the hydrogen storage bottle in the present invention;

[0065] Figure 5 for Figure 4 A partial enlarged schematic diagram of

[0066] Figure 6 It is a cross-sectional schematic diagram of the hydrogen storage bottle in the present invention;

[0067] Figure 7 for Figure 6 A partial enlarged schematic diagram of

[0068] Figure 8 It is a schematic diagram of the ceramic tank body and the ceramic tank top in the present invention.

[0069] Reference numerals:

[0070] 11. Inner liner; 12. Pressure-resistant layer; 13. First resin; 14. Ceramic layer; 141. Ceramic tank top; 142. Ceramic tank body; 15. Second resin; 16. Outer protective layer; 161. Stainless steel tank top; 162. Stainless steel tank body. DETAILED DESCRIPTION

[0071] In order to enable those skilled in the art to understand the characteristics and effects of the present application, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used herein have the common meanings understood by those skilled in the art for the present application. In case of conflict, the definitions in this specification shall prevail.

[0072] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present application in any way, that is, the content of the present application can be implemented without being limited by any specific theory or mechanism.

[0073] As used herein, "this application" means "the present invention" or "the present disclosure".

[0074] The use of "one", "an", "a kind" or similar expressions to describe the components and technical features described in this application is merely for the convenience of expression and to provide a general meaning to the scope of this application. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.

[0075] In this document, "or its combination" means "or any combination thereof", and "any one", "any one" means "any one", "any one" or "any one".

[0076] As used herein, the terms "comprises," "including," "having," "containing," or any other similar terms are open-ended transitional phrases that are intended to cover non-exclusive inclusions. For example, a composition or article containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless otherwise expressly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as being specifically disclosed and simultaneously covering closed conjunctions such as "consisting of", "consisting of", and "the remainder is", as well as conjunctions such as "consisting essentially of", "mainly consisting of", "mainly consisting of", "basically containing", "essentially consisting of", "essentially consisting of", and "essentially containing".

[0077] In this article, all features or conditions such as numerical values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions), especially integer values. For example, the range description of "1.0 to 8.0" or "between 1.0 and 8.0" or "between 1.0 and 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, etc., and should be deemed to cover endpoint values, especially sub-ranges defined by integer values, and should be deemed to have specifically disclosed individual values ​​such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, etc. Unless otherwise indicated, the foregoing method of interpretation applies to all contents of the entire application, regardless of whether the scope is broad or not.

[0078] If the quantity, concentration or other numerical value or parameter is expressed as a range, a preferred range (or a better range) or a series of upper and lower limits, it should be understood that all ranges consisting of any pair of the upper limit or preferred value (or a better value) of the range and the lower limit or preferred value (or a better value) of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0079] In this document, numerical values ​​should be understood to have the accuracy of the number of significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range of 39.50 to 40.49.

[0080] In this document, when Markush groups or optional terms are used to describe features or examples of the present application, those skilled in the art should understand that all subgroups or any individual elements in the Markush group or optional list can also be used to describe the present application. For example, if X is described as "selected from X 1 , X 2 and X 3 ", which also means that X is fully described as X 1 The claim that X is X 1 and / or X 2 and / or X 3 Furthermore, in the case of using Markush groups or optional terms to describe features or examples of the present application, those skilled in the art should understand that any combination of subgroups or individual members of all elements in the Markush group or optional list can also be used to describe the present application. Accordingly, for example, if X is described as "selected from X 1 , X 2 and X 3 If Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that X is fully described as X. 1 and / or X 2 and / or X 3 And Y is Y 1 and / or Y 2 and / or Y 3 's claim.

[0081] Unless otherwise specified, in this application, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, but not limited thereto. The interpretation of a compound in this article is not limited to a single chemical substance, but can also be interpreted as the same type of chemical substances with the same composition or the same properties.

[0082] If not otherwise specified, in this application, polymer refers to the product formed by monomer through polymerization reaction, often including many polymer aggregates, each polymer is formed by many simple structural units repeatedly connected by covalent bonds, and monomer is a compound of synthetic polymer. Polymer can include homopolymer, copolymer, prepolymer, etc., and is not limited to this. Homopolymer refers to a polymer polymerized by a monomer. Copolymer includes random copolymer (structure is such as -AABABBBAAABBA-), alternating copolymer (structure is such as -ABABABAB-), graft copolymer (structure is such as -AA(A-BBBB)AA(A-BBBB)AAA-) and block copolymer (structure is such as -AAA AA-BBBBBB-AAAAA-) etc. Prepolymer refers to a polymer with a lower molecular weight between the monomer and the final polymer, and the prepolymer contains reactive functional groups that can further undergo polymerization reaction to obtain a product with a higher molecular weight that is fully cross-linked or hardened. Polymer certainly includes oligomers, and is not limited to this. Oligomers, also known as low polymers, are polymers composed of 2 to 20 repeating units, usually 2 to 5 repeating units.

[0083] Unless otherwise specified, the "resin" in this application is a customary name for a synthetic polymer, which may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, etc., and is not limited thereto.

[0084] If not otherwise specified, in the present application, modified products include products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after copolymerization of each resin with other resins, and the like.

[0085] If not otherwise specified, the unsaturated bonds described in the present application refer to reactive unsaturated bonds, such as but not limited to unsaturated double bonds that can undergo cross-linking reactions with other functional groups, such as but not limited to unsaturated carbon-carbon double bonds that can undergo cross-linking reactions with other functional groups.

[0086] The unsaturated carbon-carbon double bonds described in the present application preferably include, but are not limited to, vinyl, vinylbenzyl, (meth)acryloyl, allyl or a combination thereof. Vinyl should be interpreted to include vinyl and vinylidene. (Meth)acryloyl should be interpreted to include acryloyl and methacryloyl.

[0087] Unless otherwise specified, the hydrocarbon groups described in this application include, but are not limited to, alkyl, alkenyl or alkynyl, and include their various isomers when interpreted. For example, a C1-C6 divalent hydrocarbon group is interpreted to include a C1-C6 divalent straight-chain hydrocarbon group, a C2-C6 divalent branched hydrocarbon group or a C3-C6 divalent cyclic hydrocarbon group. For another example, a propyl group should be interpreted to include n-propyl and isopropyl.

[0088] Unless otherwise specified, in this application, parts by weight represent relative parts by weight in a composition, which may be any weight unit, such as but not limited to kilograms, kilograms, grams, pounds, etc. For example, 100 parts by weight of polyphenylene ether resin may represent 100 kilograms of polyphenylene ether resin or 100 pounds of polyphenylene ether resin.

[0089] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present application, as long as there is no contradiction in the combination of these features.

[0090] The present application will be described below with specific implementations and examples. It should be understood that these specific implementations and examples are merely illustrative and are not intended to limit the scope of the present application and its use.

[0091] Unless otherwise stated, the methods, reagents and conditions used in the following preparation examples, comparative examples and examples are conventional methods, reagents and conditions in the art.

[0092] In the following descriptions:

[0093] Inner liner: The material is polyamide 6 (PA6), the shape is cylindrical, and the volume is available in three specifications: 420L, 505L, and 698L. The inner diameter is 72.5cm and the outer diameter of the inner liner is 73cm.

[0094] Outer protective layer: Made of 316 stainless steel, 5mm thick.

[0095] Ceramic layer material: 90% alumina, 5% silicon nitride, 5% zirconium oxide, with a tensile strength of 262MPa.

[0096] Epoxy resin: viscosity 523mPa.s (35°C), density 1.345g / mL.

[0097] Ethylenediamine: effective content ≥99%.

[0098] Phenolic resin: effective content ≥99%, compressive strength after curing 96.3MPa.

[0099] p-Toluenesulfonic acid: effective content ≥99.5%.

[0100] Carbon fiber: Model T700.

[0101] Bisphenol A epoxy vinyl resin: effective content ≥99%.

[0102] Methyl ethyl ketone peroxide: effective content ≥99.5%.

[0103] Cobalt naphthenate: effective content ≥99%.

[0104] Ammonium bicarbonate: effective content ≥99.9%.

[0105] Please refer to the attached Figures 1 to 5 The hydrogen storage material involved in the present application includes an inner liner 11, a pressure-resistant layer 12, a ceramic layer 14, and an outer protective layer 16 from the inside to the outside. The inner liner 11, the pressure-resistant layer 12, the ceramic layer 14, and the outer protective layer 16 are coaxial, and a first resin 13 is filled between the ceramic layer 14 and the pressure-resistant layer 12, and a second resin 15 is filled between the ceramic layer 14 and the outer protective layer 16, forming a hydrogen storage tank as a whole.

[0106] In the present application, the pressure-resistant layer 12 is formed by winding carbon fibers on the inner liner 11 in a wet winding manner to form an uncured pressure-resistant layer 12 , and the uncured pressure-resistant layer 12 is formed into the pressure-resistant layer 12 after degassing and curing.

[0107] In the present application, after the ceramic layer 14 is installed in the outer protective layer 16 , the second resin 15 is filled into the gap between the two, and the second resin 15 is cured at room temperature.

[0108] The ceramic layer 14 in the present application is obtained by sintering and CNC processing.

[0109] Please refer to the attached Figures 6 to 8 The ceramic layer 14 of the hydrogen storage tank involved in the present application includes a ceramic tank body 142 and a ceramic tank top 141. When the hydrogen storage tank is placed vertically, a connecting ring is provided on the top of the ceramic tank body 142 and the bottom of the ceramic tank top 141. The two connecting rings fit each other and are fixedly connected by bolts and nuts. In other embodiments, the two connecting rings can also be clamped and pressed together by a clamp.

[0110] The outer protective layer 16 of the hydrogen storage tank involved in the present application includes a stainless steel tank body 162 and a stainless steel tank top 161, and the stainless steel tank body 162 and the stainless steel tank top 161 are connected by a flange.

[0111] Example

[0112] Example 1

[0113] The components and raw materials used in this embodiment include: an inner liner 11 with a volume of 420L, a ceramic tank body 142 and a ceramic tank top 141 with an inner diameter of 73.1±0.05cm and a thickness of 50mm, a stainless steel tank body 162 and a stainless steel tank top 161, epoxy resin, ethylenediamine, phenolic resin, p-toluenesulfonic acid, carbon fiber, bisphenol A epoxy vinyl resin, methyl ethyl ketone peroxide, and cobalt cyclopentaneate.

[0114] The preparation method of this embodiment includes:

[0115] S1. At room temperature, the carbon fiber is impregnated with epoxy resin, the content of ethylenediamine in the epoxy resin is 5% of the mass of the epoxy resin, and then the impregnated carbon fiber is wound on the inner liner 11 in a manner of alternating 2 layers of hoop winding and 2 layers of spiral winding, the winding angle of the spiral winding is 16.7°, the thickness of the carbon fiber is 3 mm, and then vacuum degassing is performed at 50° C. for 1 hour to obtain an uncured pressure-resistant layer 12;

[0116] S2, curing the uncured pressure-resistant layer 12 at 110° C. for 1.5 h to obtain a cured pressure-resistant layer 12;

[0117] S3.1, after the ceramic tank body 142 and the ceramic tank top 141 are combined, they are filled with phenolic resin for infiltration, the content of p-toluenesulfonic acid in the phenolic resin is 5% of the mass of the phenolic resin, the infiltration time is 0.5h, and then the phenolic resin is poured out to obtain the ceramic tank body 142 and the ceramic tank top 141 with the inner surface coated with phenolic resin;

[0118] S3.2, loading the solidified pressure-resistant layer 12 into the ceramic can body 142, and then combining the ceramic can body 142 and the ceramic can top 141, removing the escaped resin during the process, and performing vacuum degassing at 50°C for 1 hour; then curing at 80°C, 90°C, 100°C, and 110°C for 0.5 hours respectively, and then curing at 40°C for 5 hours; obtaining the inner can;

[0119] S4.1. Install the inner tank into the stainless steel tank body 162, and then combine the stainless steel tank top 161 with the stainless steel tank body 162. The gap between the inner tank and the stainless steel tank body 162 is 5 mm.

[0120] S4.2. Fill the gap between the stainless steel tank top 161 and the inner tank with bisphenol A epoxy vinyl resin, wherein the methyl ethyl ketone peroxide in the bisphenol A epoxy vinyl resin is 2.5% of the mass of the bisphenol A epoxy vinyl resin, and the cobalt cyclohexaneate is 0.5% of the mass of the bisphenol A epoxy vinyl resin. Then, cure at room temperature for 24 hours to obtain a hydrogen storage tank.

[0121] Example 2

[0122] The difference between this embodiment and embodiment 1 is that:

[0123] The thickness of the ceramic tank body 142 and the ceramic tank top 141 used in this embodiment are both 20 mm;

[0124] In step S1, the thickness of the carbon fiber is 4 mm;

[0125] In step S4.1, the gap between the inner tank and the stainless steel tank body 162 is 15 mm.

[0126] Example 3

[0127] The components and raw materials used in this embodiment include: an inner liner 11 with a volume of 505L, a ceramic tank body 142 and a ceramic tank top 141 with an inner diameter of 73.1±0.05cm and a thickness of 35mm, a stainless steel tank body 162 and a stainless steel tank top 161, epoxy resin, ethylenediamine, carbon fiber, bisphenol A epoxy vinyl resin, methyl ethyl ketone peroxide, and cobalt cyclopentaneate.

[0128] The preparation method of this embodiment includes:

[0129] S1. At room temperature, the carbon fiber is impregnated with epoxy resin, wherein the content of ethylenediamine in the epoxy resin is 5% of the mass of the epoxy resin, and then the impregnated carbon fiber is wound around the inner liner 11 in a manner of alternating 2 layers of hoop winding and 2 layers of spiral winding, wherein the winding angle of the spiral winding is 16.7° and the thickness of the carbon fiber is 3 mm, to obtain an uncured pressure-resistant layer 12;

[0130] S2.1, after the ceramic tank body 142 and the ceramic tank top 141 are combined, they are filled with epoxy resin for infiltration, wherein the content of ethylenediamine in the epoxy resin is 5% of the mass of the epoxy resin, and the infiltration time is 0.5 h, and then the epoxy resin is poured out to obtain the ceramic tank body 142 and the ceramic tank top 141 with the inner surface coated with epoxy resin;

[0131] S2.2, loading the uncured pressure-resistant layer 12 into the ceramic can body 142, and then combining the ceramic can body 142 and the ceramic can top 141, removing the escaped resin during the process, and performing vacuum degassing at 50°C for 1.5 hours; then curing at 80°C, 90°C, and 100°C for 0.5 hours respectively, and then curing at 110°C for 1.5 hours, and then curing at 40°C for 5 hours; obtaining the inner can;

[0132] S3.1. Install the inner tank into the stainless steel tank body 162, and then combine the stainless steel tank top 161 with the stainless steel tank body 162. The gap between the inner tank and the stainless steel tank body 162 is 10 mm.

[0133] S3.2. Fill the gap between the stainless steel tank top 161 and the inner tank with bisphenol A epoxy vinyl resin, wherein the methyl ethyl ketone peroxide in the bisphenol A epoxy vinyl resin is 2.5% of the mass of the bisphenol A epoxy vinyl resin, and the cobalt cyclohexaneate is 0.5% of the mass of the bisphenol A epoxy vinyl resin. Then, cure at room temperature for 24 hours to obtain a hydrogen storage tank.

[0134] Example 4

[0135] The difference between this embodiment and embodiment 3 is that the volume of the inner liner 11 used in this embodiment is 505L.

[0136] Example 5

[0137] The difference between this embodiment and embodiment 3 is that:

[0138] The raw materials used in this embodiment also include ammonium bicarbonate;

[0139] Step S3.2: fill the gap between the stainless steel tank top 161 and the inner tank with bisphenol A epoxy vinyl resin, wherein the methyl ethyl ketone peroxide in the bisphenol A epoxy vinyl resin is 2.5% of the mass of the bisphenol A epoxy vinyl resin, the cobalt cyclohexaneate is 0.5% of the mass of the bisphenol A epoxy vinyl resin, and the ammonium bicarbonate is 10% of the mass of the bisphenol A epoxy vinyl resin, and then cure at room temperature for 24 hours to obtain a hydrogen storage tank.

[0140] Comparative Example

[0141] Comparative Example 1

[0142] The components and raw materials used in this comparative example include: an inner liner 11 with a volume of 420 L, epoxy resin, and ethylenediamine.

[0143] The preparation method of this comparative example comprises:

[0144] At room temperature, the carbon fiber is impregnated with epoxy resin, the content of ethylenediamine in the epoxy resin is 5% of the mass of the epoxy resin, and then the impregnated carbon fiber is wound on the inner liner 11 in a manner of alternating 2 layers of circumferential winding and 2 layers of spiral winding, the winding angle of the spiral winding is 16.7°, the thickness of the carbon fiber is 6 mm, and then vacuum degassing is carried out at 50°C for 1 hour, followed by curing at 110°C for 1.5 hours, and then curing at 40°C for 5 hours to obtain a hydrogen storage tank.

[0145] Comparative Example 2

[0146] The difference between this comparative example and comparative example 1 is that the vacuum degassing time is 5 hours.

[0147] Performance Testing

[0148] The hydrogen storage tanks prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were tested according to the following test items:

[0149] (1) The inner tanks prepared in Examples 1 to 2 were tested for their pressure resistance limit according to the provisions of GB / T 21596-2008, unit: MPa;

[0150] (2) The air leakage rate test was conducted at 70 MPa according to the method described in GB / T 42612-2023. The unit is NmL / (h·L).

[0151] (3) Perform static evaporation rate (LNG) test according to the method described in GB / T 34347-2017, unit: % / d;

[0152] Table 1 Partial performance of hydrogen storage tanks prepared in Examples 1 to 5 and Comparative Examples 1 to 2

[0153]

[0154] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, some simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be covered within the protection scope of the present invention.

Claims

1. A hydrogen storage material, characterized in that: The device comprises, from the inside to the outside, an inner liner (11), a pressure-resistant layer (12), a ceramic layer (14), and an outer protective layer (16); The thickness of the ceramic layer (14) is 20 mm to 50 mm, and the tensile strength of the ceramic layer (14) is ≥ 180 MPa; The inner diameter of the ceramic layer (14) is equal to or overfits with the outer diameter of the pressure-resistant layer (12); a first resin (13) is filled between the ceramic layer (14) and the pressure-resistant layer (12); and the compressive strength of the first resin (13) is ≥70 MPa; The outer protective layer (16) is a hard material, and a second resin (15) is filled between the ceramic layer (14) and the outer protective layer (16), wherein the second resin (15) comprises a vinyl resin.

2. A hydrogen storage material according to claim 1, characterized in that: The pressure-resistant layer (12) has a pressure resistance of P1, the ceramic layer (14) has a pressure resistance of P2, and P1+P2≥140 MPa.

3. A hydrogen storage material according to claim 2, characterized in that: The compressive strength of the first resin (13) is P3, 100 MPa-P1≤P3; And / or, when the hydrogen storage material stores hydrogen, the gas pressure in the inner container (11) is P4, and P4≥P1.

4. A hydrogen storage material according to claim 1, characterized in that: The first resin (13) is the resin used for the pressure-resistant layer (12).

5. A hydrogen storage material according to claim 1, characterized in that: The second resin (15) is cured at room temperature; and / or, the second resin (15) is a foamed resin; And / or, the thickness of the second resin (15) is 5 mm to 15 mm.

6. A hydrogen storage material according to claim 1, characterized in that: The material of the ceramic layer (14) is selected from one or more of aluminum oxide, silicon nitride, zirconium oxide, and silicon carbide; And / or, the material of the outer protective layer (16) is selected from metal and plastic.

7. A method for preparing a hydrogen storage material as claimed in claim 1, characterized in that: The steps include: S1, dipping carbon fiber in glue and winding it on the inner liner (11) to obtain an uncured pressure-resistant layer (12); S2, curing the pressure-resistant layer (12); S3, coating the inner surface of the ceramic layer (14) with a first resin (13), then placing the pressure-resistant layer (12) into the ceramic layer (14), and then curing the first resin (13); S4, inserting the pressure-resistant layer (12) into the outer protective layer (16), filling the second resin (15) between the pressure-resistant layer (12) and the outer protective layer (16), and then curing the second resin (15) to obtain a hydrogen storage material.

8. The method for preparing the hydrogen storage material according to claim 7, characterized in that: The uncured pressure-resistant layer (12) and the first resin (13) in step S1 are cured simultaneously. The method comprises: coating the first resin (13) on the surface of the ceramic layer (14), then loading the uncured pressure-resistant layer (12) in step S1 into the ceramic layer (14), then simultaneously degassing the pressure-resistant layer (12) and the first resin (13), and then simultaneously curing the pressure-resistant layer (12) and the first resin (13).

9. The method for preparing the hydrogen storage material according to claim 7, characterized in that: The method for coating the inner surface of the ceramic layer (14) with the first resin (13) in step S3 comprises: filling the ceramic layer (14) with the first resin (13) for infiltration for 0.5 hours, and then pouring out the first resin (13) to obtain the ceramic layer (14) with the inner surface coated with the first resin (13).

Citation Information

Patent Citations

  • High-pressure hydrogen storage bottle with prepreg tape wound around plastic liner and manufacturing method thereof

    CN111102465A

  • Enhanced hydrogen storage bottle wound with carbon fibers and sprayed with metal coating and preparation method of enhanced hydrogen storage bottle

    CN113739060A

  • Laminated hydrogen storage material hydrogen storage tank

    CN117967964A

  • Hydrogen energy storage device

    CN211976515U

  • High-pressure tank and manufacturing method of high-pressure tank

    US20210332947A1